L'immaginazione secondo Pascal: un pharmakon paradossale per l'apologetica - Steeves, Nicolas (Gregorianum, 2025)
The history of modern philosophy has often counted Pascal amongst the sworn enemies of the imagination. More recent philosophical studies, however, leading beyond the rationalism that once ruled supreme, highlight the complexity of Pascal's destructive-constructive relation to fantasy, from physics to philosophy to Christian apologetics. Derrida's metaphor of the pharmakon helps welcome this complexity and outline a few principles and guidelines for a renewed apologetics that would serve to announce the Gospel today, in the midst of the equally great complexity of our postmodern times. This should be a central task for fundamental theology.